Mycobacterial PE/PPE proteins function as “personal protective equipment” against host defenses - Resstel, Carlos; Madduri, Bala T. S. A.; Bell, Samantha L. (Frontiers in Tuberculosis, 2024)
Mycobacterium tuberculosis (Mtb) is the deadliest bacterial infection worldwide, but many molecular details of how it interacts with the innate immune system remain obscure. In particular, although Mtb secretes a large number of putative effector proteins, a relatively small number have assigned functions in facilitating host-pathogen interactions. One particularly large family of secreted mycobacterial proteins that remains poorly understood is the PE/PPE proteins. Despite numerous lines of evidence for potential roles in virulence and in mediating host-pathogen interactions, only a small fraction of these 170+ proteins have been well characterized. However, this large family of proteins is likely key for understanding how Mtb subverts immune responses, manipulates host cell biology, and establishes a successful infection. Here, we highlight examples of PE/PPEs that have well defined roles on cell intrinsic pathways in macrophages during mycobacterial infection. Examples include PPE2, which blunts production of reactive oxygen species and nitric oxide; PE_PGRS33, which facilitates bacterial uptake; PE_PGRS29, which directly binds ubiquitin to promotes host autophagy to limit pathologic inflammation; MirA, which facilitates actin tail formation to promote cell-to-cell spread; and others. Understanding the full spectrum of PE/PPE functions is critical for understanding Mtb pathogenesis and for developing new strategies to combat the worldwide TB pandemic. Advancing the lagging research efforts characterizing this mysterious family of effector proteins is critical for the TB field.